Transcription factor 4 and its association with psychiatric disorders - Teixeira, José R.; Szeto, Ryan A.; Carvalho, Vinicius M. A.; Muotri, Alysson R.; Papes, Fabio (Translational psychiatry, 2021)
The human transcription factor 4 gene ( TCF4 ) encodes a helix–loop–helix transcription factor widely expressed throughout the body and during neural development. Mutations in TCF4 cause a devastating autism spectrum disorder known as Pitt–Hopkins syndrome, characterized by a range of aberrant phenotypes including severe intellectual disability, absence of speech, delayed cognitive and motor development, and dysmorphic features. Moreover, polymorphisms in TCF4 have been associated with schizophrenia and other psychiatric and neurological conditions. Details about how TCF4 genetic variants are linked to these diseases and the role of TCF4 during neural development are only now beginning to emerge. Here, we provide a comprehensive review of the functions of TCF4 and its protein products at both the cellular and organismic levels, as well as a description of pathophysiological mechanisms associated with this gene.